Prognostic relevance of thyroid disease in adults with congenital heart disease. (14th October 2021) - Fusco, F; Scognamiglio, G; Guarguagli, S; Merola, A; Palma, M; Borrelli, N; Barracano, R; Grimaldi, N; Correra, A; Piccolo, G; La Rocca, F; Del Giudice, C; et al.
Abstract: Background: Adults with congenital heart disease (ACHD) are frequently affected by thyroid diseases (TD). However, the clinical relevance of TD in ACHD remains unknown. Purpose: We aimed to describe the prevalence of TD in the ACHD population and to ascertain whether TD are associated with worse outcome. Methods: Clinical data on all consecutive patients aged >18 years attending our ACHD unit for a day-case between 2014 and 2019 were retrospectively collected. For statistical analysis, a composite endpoint was created combining the following events at follow-up: hospitalization for heart failure, new-onset tachyarrhythmic or bradyarrhythmic events and death. Results: Four hundred ninety-five ACHD patients with a median age of 32.2 [24.5–45.6] years (46% male) were included. There was an overall prevalence of patients with moderate or complex lesions (414=84%). Compared to the group with no history of TD, patients in the TD were older, (41.9 [29.7–53.5] vs 30.2 [24.3–39] years; p<0.0001) and mainly female (77% vs 46%; p<0.0001) and more likely to have undergone at least two cardiac catheterization procedures (29 vs 13%; p<0.0001). Genetic disorders including Down syndrome were more prevalent in the group with TD (p<0.0001). Moreover, at last follow-up, those with TD had higher pro-BNP-nt values (243.5 [96.5–523] pg/ml Vs 94 [45–207] pg/ml; p<0.0001) and were in a more advanced NYHA class (27% vs 13% in class III-IV; p=0.0002). Echocardiography showed lower EF in the TD group (55 [55–60]% vs 60 [55–65]%; p=0.0002). Median follow-up was 9.4 [4.5–13.1] years. Patients with TD had a higher unadjusted mortality rate, with a trend towards statistical significance (p=0.07). Sixty-four (42%) patients in the TD group and 43 (12.5%) met our composite endpoint, leading to a 10-year survival free from events of 53.7% Vs 86.5%, respectively (p<0.0001, Figure1). Multivariate analysis showed that age, ejection fraction, previous surgical palliation, advanced physiological stage and TD were independent predictors of our composite endpoint, even after stratification for genetic disorders as reported in table1. After adjustment for baseline differences between groups with propensity matching score using age, sex, disease complexity, physiological stage, previous palliative or reparative surgery, normal or reduced systemic ventricle ejection fraction, pulmonary arterial hypertension, cyanosis and presence of systemic right ventricle as independent variables, TD remained a strong predictor of cardiac events at follow-up with an hazard ratio of 4.47 (95% CI 2.42–8.28; p<0.0001). Conclusion: TD is a strong predictor of adverse outcome in the ACHD population after exclusion of potential confounding factors, being related to a fourfold increased risk of events at follow-up. FUNDunding Acknowledgement: Type of funding sources: None.